2020
DOI: 10.21595/jmai.2020.21627
|View full text |Cite
|
Sign up to set email alerts
|

Coilgun design and evaluation without capacitor

Abstract: Capacitors with high voltage and capacity values are used in most induction coilguns that are designed and constructed. The fact that capacitors are quite bulky and slow in energy transfer and how a coilgun can be made without using capacitors is the study subject of this article. Two and four coil gun samples were made to find the essential components of an electric gun, and the results are reported in this article. The accuracy of the results is also confirmed by FEMM analysis for these models. The harmony o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These hardware features will be used more effectively with the software. In addition to security problems [18,19], development of production capabilities in sensors and software, another problem to be solved is energy management [20].…”
Section: Introductionmentioning
confidence: 99%
“…These hardware features will be used more effectively with the software. In addition to security problems [18,19], development of production capabilities in sensors and software, another problem to be solved is energy management [20].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the launching mass and energy can be extended, but the speed remained low. Research [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] has shown results of simulations and related experiments aimed at increasing launching velocity and energy (Fig. 1).…”
mentioning
confidence: 99%